Comparison of magnetized and normal water on yield and yield components of banana and hydraulic performance of drip irrigation system - Khalifa, Ahmed B. A.; Ali, Mohamed A; Babiker, IImadeldin Ahmed A; Ahmed Elhag, Fisal M (Gezira Journal of Agricultural Science; Vol 14 No 1 (2016), 2016)
An experiment was conducted at the Horticultural Research Centre Farm of the Agricultural Research Corporation (ARC), Wad Medani, Sudan during seasons 2010 through 2012 to evaluate effects of magnetic water technology on yield, and yield components of banana cv. Albeily and hydraulics of drip irrigation system. Two types of irrigation water were used: magnetic water and normal water. The plot of each type of irrigation water consisted of 4 banana plants. The two treatments were replicated 5 times. The results revealed that applying magnetic water increased plant height and girth of banana and attained fewer days from planting to flowering and from flowering to harvest compared to normal water. Bunch weight and number of hands per bunch were also higher for magnetic water.  Magnetic water improved the hydraulic performance of drip irrigation system compared to normal water.        اجريت هذه الدراسة بمزرعة مركز بحوث البساتين، هيئة البحوث الزراعية، واد مدني السودان في الفترة من 2010 وحتي 2012 لتقييم أثر تقنية مغنطة المياه على الانتاجية  ومكونات انتاجية الموز والاداء الهيدرولوكي للري بالتنقيط صنف البيلي. استخدم نوعين من مياه الري مياه ممغنطة ومياه عادية. الوحدة في كل نوع من مياه الري ضمت اربع نباتات والمعاملتين تم تكرارها خمس مرات. اظهرت النتائج ان المياه الممغنطة ادت الي زياده في طول وسمك الساق الكاذبة للموز وكذلك الي تقليل الايام من الزراعة الي الازهار ومن الازهار الي الحصاد. كما اظهرت النتائج ان وزن السبيطة وعدد الكفوف في السبيطة كان اعلي تحت المياه الممغنطة. أدت مغنطة مياه الري الي تحسين الاداء الهيدرولوكي لنظام الري بالتنقيط مقارنة مع المياه العادية.